PERANAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM PENGEMBANGAN STAF SMPN 18 SEMARANG - Risnawati, V Naniek (Sekolah Tinggi Ilmu Ekonomi Semarang, 2009)
Supervision    is   meant   to   help   and   develop   teachers   to   be professional. With professional teachers, the final objective of supervision to   improve   student's    learning   could   be   achieved.   The   principal's responsibility  as a supervisor  is to help teachers  develop  their teaching capability. From the observation, it is found that a lot of principals have not conducted  their supervision  properly. Therefore,  it is worth studying